2016
DOI: 10.1039/c6dt00225k
|View full text |Cite
|
Sign up to set email alerts
|

Use of a 4,5-dicyanoimidazolate anion based ionic liquid for the synthesis of iron and silver nanoparticles

Abstract: Sixteen new ionic liquids (ILs) with tetraethylammonium, 1-butyl-3-methylimidazolium, 3-methyl-1-octylimidazolium and tetrabutylphosphonium cations paired with 2-substituted 4,5-dicyanoimidazolate anions (substituent at C2 = methyl, trifluoromethyl, pentafluoroethyl, N,N'-dimethyl amino and nitro) have been synthesized and characterized by using differential scanning calorimetry (DSC), thermogravimetric analysis (TGA). The effects of cation and anion type and structure of the resulting ILs, including several r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…This systematic approach to variation of the C2‐substituent led to azolate ILs with the broadest liquidus ranges of the salts reviewed in this paper (see Table ). This was achieved firstly by the use of a tetrabutylphosphonium cation, which is well‐known for its thermal stability, but more relevant to this review, the substitution of the imidazolate ring with ‐CF 3 , ‐C 2 F 5 , ‐N(CH 3 ) 2 , or ‐CH 3 groups contributed significantly to both the suppression of the glass transition temperatures (to as low as −72 °C for tetrabutylphosphonium 2‐trifluoromethyl‐3,5‐dicyanoimdazolate, [P 4,4,4,4 ][2‐CF 3 ‐4,5‐diCN‐im]), and increased thermal stability (up to 403 °C for tetrabutylphosphonium 2‐methyl‐3,5‐dicyanoimidazole, [P 4,4,4,4 ][2‐CH 3 ‐4,5‐diCN‐im]) …”
Section: Structural Features and Propertiesmentioning
confidence: 89%
See 1 more Smart Citation
“…This systematic approach to variation of the C2‐substituent led to azolate ILs with the broadest liquidus ranges of the salts reviewed in this paper (see Table ). This was achieved firstly by the use of a tetrabutylphosphonium cation, which is well‐known for its thermal stability, but more relevant to this review, the substitution of the imidazolate ring with ‐CF 3 , ‐C 2 F 5 , ‐N(CH 3 ) 2 , or ‐CH 3 groups contributed significantly to both the suppression of the glass transition temperatures (to as low as −72 °C for tetrabutylphosphonium 2‐trifluoromethyl‐3,5‐dicyanoimdazolate, [P 4,4,4,4 ][2‐CF 3 ‐4,5‐diCN‐im]), and increased thermal stability (up to 403 °C for tetrabutylphosphonium 2‐methyl‐3,5‐dicyanoimidazole, [P 4,4,4,4 ][2‐CH 3 ‐4,5‐diCN‐im]) …”
Section: Structural Features and Propertiesmentioning
confidence: 89%
“…This indicated a chemical stability mechanism, whereby Ti 0 donates electron density to the nitrate group, with the partially reduced oxygen atom bridging the newly oxidized Ti surface, thus stabilizing the NP. Although the cyano‐substituted azolates, were less effective for stabilization of Ti NPs, the IL [C 8 mim][2‐CH 3 ‐4,5‐diCN‐im] has recently been used successfully with other metals . Nanoparticles of both Fe (1.8±0.8 nm) and Ag (4.0±1 nm) were successfully prepared in this IL, with the narrow size distributions indicating controlled and ordered NP growth in these ILs capable of stabilizing NP growth through the cyano groups and anion π‐system.…”
Section: Applications Of Azolate Ilsmentioning
confidence: 99%
“…Besides application in classic solid state chemistry, ILs can be used as reaction media to prepare (oligomeric) metal complexes, metal organic frameworks, coordination polymers [25–35] or cluster compounds incorporating main group elements [36–41] . Within SPP 1708, the synthesis of intermetallic cluster and nanoparticles, [3,42–56] the controlled synthesis of polyanions and cations, [57–61] solvent‐free chalcogenidometal‐containing materials, [62–75] deposition of nanocrystalline materials, [76–80] ionic liquids as precursors for inorganic materials, [81–83] ionic‐liquid‐modified hybrid materials, [84–87] as well as the low‐temperature synthesis of thermoelectric materials [88–92] were investigated. Moreover, theoretical [93–106] and solubility [107–114] aspects during the synthesis process were studied.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, ionic liquids (ILs) have become a hot research topic among multidisciplinary areas, including chemistry, physics, biology, engineering, and so on, and have radically changed the concept of the nature of liquids. , Owing to special physicochemical properties, the ionic liquids provide a useful platform for fabricating various nanostructured materials and catalysts, which sometimes are difficult to realize by conventional solvents. Zhao et al used eutectic mixtures with similar properties to ionic liquids for synthesizing Ni 2 P nanoparticles from nickel hypophosphite. To date, most of the studies have focused on the imidazolium ILs; however, phosphonium-based ILs are found to exhibit more superiority in organic synthesis, CO 2 /CO capture, and nanomaterial synthesis than imidazolium ILs in some reactions. Meanwhile, phosphonium-based ILs, similar to the imidazolium ILs, have strong microwave absorbing ability, and microwave-driven ionothermal synthesis is an alternative approach to offer various opportunities for the synthesis of inorganic nanomaterials. , For example, Ding et al successfully synthesized micro-/nanostructured metal chalcogenides upon microwave heating using phosphonium ILs as solvent.…”
Section: Introductionmentioning
confidence: 99%